Work-Related Stress and Substance Use as Risk Factors for Chronic Disease Among Three-Wheel Drivers in Galle, Sri Lanka: A Qualitative Study - Kirkorowicz, JM; Sapukotana, P; De Silva, PV; Noda, M; de Oliveira, JS; Østbye, T (International Journal of Occupational Safety and Health, 2014)
Background: Motor three-wheel drivers provide an important means of transportation in Sri Lanka, comprising 15% of motorized road vehicles. Although three-wheel driving is a widespread occupation for Sri Lankan men, little is known about their general health or risk factors. Objectives: This paper investigates chronic illnesses and risk factors for such illnesses in a sample of 33 three-wheel drivers in Galle, Sri Lanka. Methods: A qualitative investigation was conducted between June and August 2012. 20 three-wheel drivers participated in 60-minute semi-structured interviews, and 13 participated in semi- structured focus groups related to their work-related health concerns. Results: Illness reported included musculoskeletal pain, hypercholesteremia, hypertension, and diabetes. Participants identified work-related stress and substance abuse as risk factors. Conclusions: Participants described a cycle of work related stress, substance use, and chronic illness. Community-based education on the risks of substance use and alternative means of coping may be an effective intervention for these workers. DOI: http://dx.doi.org/10.3126/ijosh.v3i2.7662